Evaluating WebAssembly for Orchestrated Deployment of Serverless Functions - Kjorveziroski, Vojdan; Filiposka, Sonja; Mishev, Anastas (IEEE, 2022)
Serverless computing has made a significant impact in the cloud computing landscape, and has even been extended beyond the cloud, up to the edge of the network. Existing serverless platforms which use containers and micro virtual machines as function runtimes incur a significant startup latency, hindering the performance and scalability of the executed functions. One potential solution to this problem is the use of WebAssembly. In this paper we discuss recent developments which allow WebAssembly to be used for serverside applications, as well as serverless functions, and evaluate potential orchestration options with the end goal of integrating WebAssembly with existing cloud and edge infrastructure. We conclude that while WebAssembly is a solution to the cold start problem, further work is needed in this area. To realize the endgoal of seamless and user-friendly serverless platforms that can be deployed across the edge-cloud continuum and can dynamically adapt to compute and latency requirements, WebAssembly should not be seen as the exclusive technology, and instead multiple runtime environments should be supported in addition to WebAssembly.
© 20XX IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.
Keywords: WebAssembly; Serverless Computing; Function as a Service; Cloud Computing; Edge Computing; Internet of Things